Radio Frequency Utilization for the Development of Smart Grid in Thailand - เบญจพลกุล, วาทิต (Journal of Digital Communications, 2018)
Smart grid is an advanced technology to address the challenges of future power grid, such as increase of electricity demand and intermittent of small distributed energy resources. Smart grid utilizes information and communication technologies to enhance the power grid to be smart and enable grid management to ensure stability and reliability as well as maintain energy security of the country. Wireless communications play an important role to support machine-to-machine communications in smart grid network, therefore, frequency allocation for smart grid development is crucial issue that must be considered and clearly defined by all relevant parties. In this paper, we study and develop recommendation about guideline of radio frequency utilization for the development of smart grid in Thailand which is divided into three approaches: 1) the use of unlicensed frequency, 2) the use of licensed frequency, and 3) the use of radio frequency of telecommunication operators who have licenses, by considering the importance of data and the objective of various smart grid applications.